Facility Layout Redesign Reduces Material Handling Distance: Perancangan Ulang Tata Letak Fasilitas Mengurangi Jarak Pengangkutan Material - Inggrit Ananda Rahmadita; Atikha Sidhi Cahyana (Indonesian Journal of Innovation Studies, 2025)
General Background: Facility layout design plays a crucial role in improving operational efficiency and material flow within production systems. Specific Background: Ineffective layout arrangements can lead to excessive material handling distances and reduced productivity. Knowledge Gap: Previous studies have addressed layout optimization methods, but limited analysis focuses on practical implementation using Activity Relationship Chart for specific production settings. Aims: This study aims to redesign the facility layout using the Activity Relationship Chart method to minimize material movement distance. Results: The proposed layout demonstrates a reduction in material handling distance compared to the initial layout, indicating improved efficiency in production flow. The analysis also shows better arrangement of activity relationships and space utilization. Novelty: This study provides a practical application of ARC-based layout redesign in a specific production context with measurable improvements. Implications: The findings support decision-making in facility planning to achieve more efficient production systems and reduced operational inefficiencies. Keywords: Facility Layout, Material Handling, Activity Relationship Chart, Production Efficiency, Layout Redesign Key Findings Highlights Proposed arrangement shortens movement path between workstations Activity relationships guide spatial configuration decisions Improved workflow structure observed after redesign